2009
DOI: 10.5511/plantbiotechnology.26.395
|View full text |Cite
|
Sign up to set email alerts
|

A domain containing the ESR motif in ENHANCER OF SHOOT REGENERATION 1 functions as a transactivation domain

Abstract: The Arabidopsis ENHANCER OF SHOOT REGENERATION 1 (ESR1) gene is thought to regulate the initiation of in vitro shoot regeneration. ESR1 encodes a transcriptional activator belonging to the ETHYLENE-RESPONSIVE FACTOR family. In this study, we investigated the functions of the C-terminal domain of the ESR1 protein. Effectorreporter assays using the GAL4 DNA-binding domain fused with portions of the C-terminal domain revealed that the ESR motif, which is a short amino acid sequence commonly seen in the C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…DRNL and its paralogue DORNRÖSCHEN (DRN), have highly redundant roles in embryonic patterning and cotyledon organogenesis (Chandler et al 2007). Both genes also have discrete roles, integrating differentially in directional auxin transport and CUC pathways during cotyledon initiation , both proteins possess a C-terminal activation domain (Matsuo and Banno 2008;Nomura et al 2009) and DNA binding has been shown for DRN ). This paper shows that DRNL transcription pre-patterns incipient floral primordia, with the number of expressing cells correlating to previous estimations of floral organ founder cells.…”
Section: Introductionmentioning
confidence: 94%
“…DRNL and its paralogue DORNRÖSCHEN (DRN), have highly redundant roles in embryonic patterning and cotyledon organogenesis (Chandler et al 2007). Both genes also have discrete roles, integrating differentially in directional auxin transport and CUC pathways during cotyledon initiation , both proteins possess a C-terminal activation domain (Matsuo and Banno 2008;Nomura et al 2009) and DNA binding has been shown for DRN ). This paper shows that DRNL transcription pre-patterns incipient floral primordia, with the number of expressing cells correlating to previous estimations of floral organ founder cells.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, ERF12 and the combined functions of DRN, DRNL and PUCHI are opposing in terms of the repression and promotion of organ initiation, respectively. DRN, DRNL and PUCHI are considered to be transcriptional activators (see Chandler 2018) and all contain a transcriptionally active ESR domain (Nomura et al 2009). Conversely, ERF12 contains a C-terminal EAR-like repressor domain, which might transcriptionally repress downstream targets at the timepoint of incipient FM development within the IM, which is associated with large-scale gene downregulation (Wellmer et al 2006).…”
Section: Erf12 Interacts Genetically With Closely Related Erf Factorsmentioning
confidence: 99%
“…ESR1 encodes a TF belonging to the ERF family. The region between the AP2/ERF domain and the ESR motif in ESR1 is indicated to be essential for enhancement of shoot regeneration [ 30 ]. ESR1 acts as a transcriptional activator [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%